URGENSI SASTRA DIGITAL MELALUI MATA KULIAH MENULIS SASTRA UPAYA MEMBENTUK KARAKTER MAHASISWA - Ulinnuha, Ulinnuha; Romdhoningsih, Diana; Mahpudoh, Mahpudoh; Sari, Riska Emelda; Irawan, Alvi Heranamawati; Asi, Rindi Santi (Teks: Jurnal Penelitian Pendidikan Bahasa Indonesia, 2024)
The fact in the world of work, system changes continue to be made by companies in order to adapt to current conditions. However, the changes made actually make everyone involved exhausted. Coupled with the tension, fear, and struggle within the current young generation. So society, especially young people, needs to have strong competence and character to face the new world. So the result of the rapid change called the Vuca era. In relation to this, this study aims to prepare the younger generation, especially students, to be able to face the Vuca era by prioritizing the quality of character education through digital literature that is relevant to the mastery of literary writing courses in universities. The method used is qualitative descriptive. The results show that through the subject of writing literature based on digital literature, students gain learning experiences that can build character education to prepare them to face the Vuca era. It can be concluded that from all the elements contained in the literary writing course such as course descriptions, learning achievements, to the core material of the literary writing course, it is relevant to the concept of digital literature which aims to study literature in accordance with the development of world technology and this productive nature can dispel concerns about facing the VUCA era. This means that by productively writing literature on social media, you will become accustomed to new experiences, new situations, social symptoms through writing, always paying attention to requests for writing ideas, writing styles that are in demand by readers of each generation. So that it becomes a solution to the concerns and pessimistic feelings of the younger generation in facing the VUCA Era.